(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
Water quality change is caused by indirectly or directly sources such as human activities, uncontrolled sewage, or heavy metals and sediments. This study was conducted at two famous ecotourism places in Jeli, Kelantan which are Lata Janggut and the new ecotourism place, Lata Keding. The main objective of this study is to compare water quality index and heavy metals at the cascades. Twelve samples were collected from two points which are flowing water and stagnant water in each cascade. Mann Whitney test was used to determine whether there are significant differences in concentration of each physical and chemical parameters between Lata Keding and Lata Janggut. Spearman correlation was also used to determine the relationships between physical and chemical parameters. This study found that Water Quality Index (WQI) in Lata Janggut is 69.07 (Class III) and Lata Keding is 71.75 (Class III) which means that the water quality was slightly polluted for both cascades. Therefore, Lata Janggut and Lata Keding require extensive treatment if it will be used for water supply but still under control and safe to had body contact with the water. However, further monitoring are needed to avoid any environmental issues arise.